Effect of Child Neglect on Learning Outcomes of Pupils of Kamwezi Sub-County Rukiga District. - Karugaba, Dickson (Kabale University, 2025)
The purpose of the study was to find out the effect of child neglect on the learning outcomes of pupils in Primary schools in Kamwezi sub-county, Rukiga District. The study was guided by the following study objectives; to identify the causes of Child neglect in the Kamwezi sub-county Rukiga district, to identify whether child neglect has an impact on learning outcomes in the Kamwezi sub-county Rukiga district, and to explore intervention programs that educators can use to help children who have been victims of child neglect. The study used a descriptive research survey using both qualitative and quantitative approaches. It involved respondents who gave their views, facts, and opinions that were assessed. The Population of this study comprised parents, guardians,s and teachers in selected schools of Kamwezi Sub-county, Rukiga District who were added up to get 60 because they were the basis of the study and this provided the relevant answers to the study questions. In order for this to be achieved, the researcher used 50 respondents using Krejcie and Morgan's table 1970. Data collection tools used included questionnaires, interview guides, and documentary reviews. The study revealed that the main causes of child neglect inthe Kamwezi sub-county Rukiga district are poverty, lack of parental education, and parental substance abuse. These factors were found to be significant predictors of child neglect, with poverty being the most significant contributor. The study found that many parents in the sub-county struggle to provide basic needs for their children, leading to neglect. The study recommended that educators and policymakers implement intervention programs aimed at supporting children who have been victims of child neglect. These programs should focus on providing emotional and psychological support to neglected children, as well as providing them with basic needs such as food, clothing, and shelter. The study also recommends that educators and policymakers provide training and education to parents on responsible parenting and child care.